NEW PERIODICALS. - Mayhood, Erin (Notes, 2006)
Presents a list of music periodicals and their objectives, formats and contents and provides information on special issues, title and format changes and cessations. "Acoustics Research Letters Online," edited by D. Keith Wilson; "Directory of Open Access Journals"; "Music in Art: International Journal for Music Iconography."